Role and location of the unusual redox-active cysteines in the hydrophobic domain of the transmembrane electron transporter DsbD - Katzen, Federico (National Academy of Sciences, 2003)
The central hydrophobic domain of the membrane protein DsbD catalyzes the transfer of electrons from the cytoplasm to the periplasm of Escherichia coli. Two cysteine residues embedded in transmembrane segments are essential for this process. Our results, based on cysteine alkylation and site-directed proteolysis, provide strong evidence that these residues are capable of forming an intramolecular disulfide bond. Also, by using a combination of two complementary genetic approaches, we show that both cysteines appear to be solvent-exposed to the cytoplasmic side of the inner membrane. These data are inconsistent with earlier topological models that place these residues on opposite sides of the membrane and permit the formulation of alternate hypotheses for the mechanism of this unusual transmembrane electron transfer.